ОБГРУНТУВАННЯ РАЦІОНАЛЬНИХ РОЗМІРІВ МАГНІТОПРОВОДУ КІЛЬЦЕВОГО РОТОРА ВІТРОЕЛЕКТРИЧНОГО ВЕНТИЛЬНОГО РЕАКТИВНОГО ГЕНЕРАТОРА - Козирський, В.В.; Подольцев, О.Д.; Трегуб, М.І. (Інститут електродинаміки НАН України, Київ, 2018)
The effect of geometric dimensions of the ferromagnetic elements of ring-shaped rotor of the switched reluctance generator on the multiplicity of the variation of magnetic circuit conductivity caused by rotor motion is studied by numerical simulation using finiteelement method and experimental prototype. The quantitative relations of dimensions of the elements with square cross-section are determined to provide the maximum change in magnetic system conductivity at rotor motion and to improve the electromagnetic characteristics of the generator. References 7, figures 5.